Hubungan Pemberian Reward dan Punishment terhadap Motivasi Belajar Siswa di SMP Negeri X - Dena Septianidar; Abd Basith; Dewi Mariana (Journal Innovation In Education, 2025)
This study aims to analyze the relationship between reward and punishment on students' learning motivation at SMP Negeri X. The background of the study is based on the importance of motivation in the learning process, because motivation plays a major role in influencing students' enthusiasm and participation. Rewards and punishments are seen as educational instruments believed to help improve or decrease certain behaviors in an academic context. Motivation in learning is a key factor that influences students' performance and engagement in the classroom. The research method used is a quantitative correlational with an asymmetrical associative relationship design. The study population included 123 ninth-grade students, and through a simple random sampling technique using the Slovin formula, a sample of 94 students was obtained. The research instrument was a Likert-scale-based questionnaire, consisting of 30 statements for reward and punishment variables with a reliability of 0.952, and 28 statements for learning motivation variables with a reliability of 0.974. Data analysis was carried out through simple regression, F-test, and coefficient of determination (R²). The results showed that the provision of rewards and punishments was in the "sufficient" category with an average score of 96.20 (range 91–100). Similarly, student learning motivation was classified as "sufficient" with an average score of 88.89 (range 85–92). The hypothesis test yielded an Fcalculated of 0.058, which is smaller than the Ftable of 3.94 at the 5% significance level. This indicates no significant relationship between the two variables. The R² value of 0.6% indicates that the contribution of rewards and punishments to learning motivation is very low. These findings suggest that teachers should explore alternative strategies to foster students' intrinsic motivation. Thus, this study emphasizes the need for motivational strategies other than rewards and punishments to increase student learning participation.